Students’ Experiences and Perceptions of Boredom in EFL Academic Context - Amiri, Elmakki; ELKARFA, Abderrahim; Sbaihi, Mohamed; Iannàccaro , Gabriele; TAMBURINI, Elena (International Journal of Language and Literary Studies, 2022)
Academic boredom has captured the attention of psychologists. It is one of the most neglected and underexplored emotions in educational settings. As such, drawing on research findings from related domains, boredom can be seen as a prevalent, deactivating and negative emotion whose detrimental impact affects students’ academic learning and performance (see Pekrun, Goetz, Daniels, Stupnisky & Perry, 2010). The present study investigated students’ perceptions and experiences of boredom in university students. The study also explored different antecedents causing boredom and different coping strategies that students use to cope with it utilizing a mixed-method approach. Quantitative data were collected utilizing a recently designed and validated instrument: Foreign Language Learning Boredom Scale (see Li, Dewaele & Hu, 2021). The sample consisted of 190 Moroccan university students from three countries. Qualitative data were collected through semi-structured interviews with 13 university students describing their experiences of academic boredom. The findings revealed that boredom is pervasive among university students and seen as a complex handicap that may affect the overall well-being of students even though they generally displayed moderate levels of boredom. As such, the findings have also shown several proximate factors and reasons that act as precursors of foreign language learning boredom, including homework, under-challenging and/or over-challenging or meaningless task, teacher-dislike, and PowerPoint presentations. The findings revealed that students used cognitive and behavioural coping strategies to cope with boredom. It is important to note that sometimes students opted for both strategies to combat this negative emotion. Moreover, teachers were also seen as important elements who directly contribute to students’ fight against boredom through creating an emotionally safe and supportive environment. Implications for future research and educational practice are also discussed.